Ulama Hadis dalam Kontestasi Keagamaan Digital Mesir: Studi Kasus Sheikh Ma’bid ‘Abd al-Karīm - Muhamad Khoirul Huda (Refleksi: Jurnal Kajian Agama dan Filsafat, 2024)
This article seeks to explain the context of the emergence of neo-traditionalist hadith scholars in Egypt’s digital socio-political-religious space. The analysis focuses on Sheikh Ma’bid ‘Abd al-Karīm, an al-Azhar hadith scholar who is nicknamed “Sheikh al-Majālis al-Ḥadīthiyyah”. Using a qualitative approach and literature study methods, the analysis finds that the presence of Sheikh Ma’bid ‘Abd al-Karīm in the digital space cannot be separated from the diverse context of contemporary Egyptian religious authority contestation. Sheikh Ma’bid is part of the voice of a wider network of clerics known as “Neo Islamic Traditionalism” centered at Al-Azhar under the leadership of Sheikh Aḥmad Ṭayib. The Islamic neo-traditionalism movement is a reassertion of al-Azhar’s religious identity and authority which had dimmed amid the rise of various currents of Islamic thought, especially transnational-Salafi. Shaykh Ma’bid plays an important role in maintaining al-Azhar’s symbolic authority in the field of hadith studies through the digital content he creates.